Stevens' Poetry of Thought - Doggett, Frank (Johns Hopkins University Press, 2020)
Originally published in 1966. Stevens' Poetry of Thought is the first full-length study of Wallace Stevens as a thinker. With original insight, Mr. Doggett provides many detailed interpretations of individual poems in examining Steven's imagery. This is a pertinent treatment of Stevens' inherent affinity with the philosophic imagination of his time, showing how firmly this poet was linked through his images with the leading thinkers of the age just passed-especially Schopenhauer, Bergson, Santayana, Whitehead, William James, Jung, and Cassirer. The clear and perceptive reading of a great many of the poems in this book should illuminate the work of Stevens for all the readers who admire his language and wish for further insight into its significance. Beyond being a definitive exposition of Steven' poetry and a meaningful act of faith in the intellectual sophistication of Stevens, this is an exciting study of the human imagination which satisfies the need for distinction between poetry and philosophy while illuminating one by the other. Mr. Doggett demonstrates how the poetry of Stevens is a representative voice of the ideas of his age and illustrates Stevens own statement: "Poets and philosophers often think alike, as we shall see." Wallace Stevens is now recognized as one of the most important American poets of the twentieth century. His first volume of poems, Harmonium was published in 1923, and since then seven volumes of his work have appeared. He was awarded the Bollingen Prize in Poetry of the Yale University Library for 1949. In 1951 he won the National Book Award in Poetry for The Auroras of Autumn. The Collected Works of Wallace Stevens was awarded the Pulitzer Prize in Poetry in 1955. From 1916 to his death in 1955 he was associated with the Hartford Accident and Indemnity Company, of which he became vice-president in 1934.